2018
DOI: 10.31557/apjcp.2018.19.12.3383
|View full text |Cite
|
Sign up to set email alerts
|

CD200 Expression in Diagnostic and Prognostic Assessment of Mature B Cell Lymphophoproliferative Neoplasms

Abstract: Background:Multiparameter flow cytometry is a useful tool for diagnostic evaluation of mature B-cell neoplasms (MBN). Recently, it has been shown that assessment of CD200 expression may improve the distinction between chronic lymphocytic leukemia (CLL; CD200 positive) and mantle cell lymphoma (MCL; CD200 negative), but any potential as a prognostic marker for CLL remains to be established. Materials and methods: This cross sectional study was conducted on sixty-seven patients newly diagnosed as having mature B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…In line with this, absence of the CD200/CD200R inhibitory axis results in enhanced anti-tumor responses (Kretz-Rommel et al, 2007;McWhirter et al, 2006;Petermann et al, 2007;Rygiel et al, 2012). Coherently, tumor CD200 expression in multiple human cancers is associated with poor prognosis (Aref et al, 2018;Chen et al, 2017;El Din Fouad et al, 2018;Moreaux et al, 2006) and blocking the CD200/CD200R inhibitory axis has been proposed as checkpoint blockade therapy in human cancer (Mahadevan et al, 2019).…”
Section: Introductionmentioning
confidence: 80%
“…In line with this, absence of the CD200/CD200R inhibitory axis results in enhanced anti-tumor responses (Kretz-Rommel et al, 2007;McWhirter et al, 2006;Petermann et al, 2007;Rygiel et al, 2012). Coherently, tumor CD200 expression in multiple human cancers is associated with poor prognosis (Aref et al, 2018;Chen et al, 2017;El Din Fouad et al, 2018;Moreaux et al, 2006) and blocking the CD200/CD200R inhibitory axis has been proposed as checkpoint blockade therapy in human cancer (Mahadevan et al, 2019).…”
Section: Introductionmentioning
confidence: 80%
“…As reported in Table 3, correlations were found with some clinical-biological features of CLL patients with <50% CD200+ cells. In contrast, using the same methodological approach, El Din Fouad et al found other correlations in patients with a lower percentage of CD200+ CLL cells (<50%) (74). Moreover, while the former study did not report data on TTT, response to therapy or OS, the latter found no correlation with response to treatment or OS.…”
Section: Cd200 and Prognosis In Cllmentioning
confidence: 89%
“…Alterations between OX2 and its OX2R receptor were found in both PD and AD. Precisely in this regard, studies have been carried out to study how the OX2-OX2R system determines a greater probability of the appearance of neurodegenerative diseases [67,90]. The well-established PD model that leads to the neurodegeneration of dopaminergic neurons is induced by intragastrically administered rotenone [91] or 6-hydroxydopamine (6-OHDA).…”
Section: Orexin In Microglia Activationmentioning
confidence: 99%